Local Government System in India, Pakistan, and Bangladesh: A Comparative Study - Saikat Roy (KILA Journal of Local Governance, 2015)
Decentralization is a widely used concept, and it is closely linked with democracy, development and good governance. Many research findings clearly demonstrate that decentralization provides an institutional mechanism through which citizens at various levels can organize themselves and participate in the decision making process. The present study examines the dimension of the decentralization process and local government system in India, Pakistan and Bangladesh from a comparative perspective.